Tanke plasti klasičnih superprevodnikov - Midden, Marion van (Matrika, 2014)
Basic properties of condutors and superconductors are presented. The main properties and theories of superconductivity are described. Finally, the experiment that showed a superconductive gap in layers as thin as one atomic monolayer is presented.
Keywords: conductivity; prevodnost; superconductivity; superprevodnost; tanke plasti; thin layers